(untitled) (Journal of Engineering, 2014)
Planning for a city with human identity considers the needs of human being that exist in the traditional cities where it was so easy creating place there, on the other hand, modern cities refuse these values and reduce the human characters of urban fabric elements , and the searching for the concept of " Urban Coherence " considers the knowledge about urban theory, especially Morphological attitudes finding three sides of making the coherence of dense urban fabric which are " Functional Complementarily , Formal Complementarily , Contextual complementarily “and the differentiation of these sides within the variety of spatial structural patterns between the organic type of traditional city and the gridiron type of modern city. To approve the hypothesis of the research, the theoretical frame was